Business organisation performance behaviour indicators in Ghana and Kenya: A comparative analysis. Issue 1 (2nd January 2022) - Anafo, Solomon Abugre; Tian, Yixiang; Ahia, Bright Nana Kwame
Abstract : We examined business organisation performance indicators across two African countries (Ghana and Kenya) with diverse and volatile economic variables. Utilising secondary data from 2007 to 2017, we applied fixed-effect panel regression to predict profitability indicators from business operations. Our findings indicated that operating cost per sales and assets had a negative relationship with profitability; while liquidity and sales had a positive relationship with profitability as measured by return on assets and profit margins in both countries. In Ghana, economic behavioural indicators, inflation, and exchange rate had a negative effect on return on assets; whereas currency in circulation, trade openness, and country competitiveness had a positive relationship with return on assets. In Kenya, the exchange rate had a negative non-significant relationship with profit margin, while currency in circulation was significantly and positively correlated with profit margin. Firm-specific variables (operating cost, assets, and sales) and macro-economic variables (inflation, exchange rate, currency in circulation, trade openness, and country competitiveness) appear to have an influence on the market behaviours of business organisations in two African countries.